(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
The attribute granted to school principals to care and look after children and teenagers who are under their direct care, explains the facts that some judicial ordering often compel them to respond for harms that could affect pupils. This obligation is often established, on the basis of neglecting duty of care. Nevertheless, if there is a case of sexual violence inside the school, the approach of the problem turns more complex, because it must be proven not only the lack of appropriate action -by not complying the applicable protocol for this cases-, but also the rol as guarantor of the active subject. This article covers those particularities, and studies the case of Paola Guzmán Albarracín, deplorable example of ecuadorian administrative and jurisdictional authorities’ inaction, that lead to severe violations of the victim’s human rights. Thereon, the decision of the Inter-American Human Rights Court established a turning point that reopens the debate about the need to properly charge all perpretators of sexual-based violence, committed by those who hold management position in educational institutions.